From Verbal Account to Written Evidence: Do Written Statements Generated by Officers Accurately Represent What Witnesses Say? - Milne, Rebecca; Nunan, Jordan; Hope, Lorraine; Hodgkins, Jemma; Clarke, Colin (Frontiers in Psychology, 2022)
Most countries compile evidence from witnesses and victims manually, whereby the interviewer assimilates what the interviewee says during the course of an interview to produce an evidential statement. This exploratory research examined the quality of evidential statements generated in real world investigations. Transcribed witness/victim interviews (N = 15) were compared to the resultant written statements produced by the interviewing officer and signed as an accurate record by the interviewee. A coding protocol was devised to assess the consistency of information between what was said by the interviewee in the verbal interview and what was reported in the written statement. Statements contained numerous errors including omissions, distortions, and the inclusion of information not mentioned in the verbal interview. This exploratory work highlights an important area for future research focus.